"What Do People Do If They Don't Have Insurance?": ED‐to‐ED Referrals. (4th October 2017) - Medford‐Davis, Laura N.; Prasad, Siddharth; Rhodes, Karin V.
Abstract: Objective: Up to 20% of patients seen in public emergency departments (EDs) have already been seen for the same complaint at another ED, but little is known about the origin or impact of these duplicate ED visits. The goals of this investigation were to explore 1) whether patients making a repeat ED visit are self‐referred or indirectly referred from the other ED and 2) gather the perspective of affected patients on the health, social, and financial consequences of these duplicate ED visits. Methods: This mixed‐methods study conducted over a 10‐week period during 2016 in a large public hospital ED in Texas prospectively surveyed patients seen in another ED for the same chief complaint. Selected patients presenting with fractures were then enrolled for semistructured qualitative interviews, which were audiotaped, transcribed, and independently coded by two team members until thematic saturation was reached. Results: A total of 143 patients were identified as being recently seen at another local ED for the same chief complaint prior to presenting to the public hospital; 94% were uninsured and 61% presented with fractures. A total of 27% required admission at the public ED and 95% of those discharged required further outpatient follow‐up. Fifty‐one percent of patients completed a survey and qualitative interviews were conducted with 23 fracture patients. Fifty‐three percent of patients reported that staff at the first hospital told them to go the public hospital ED, and 23% reported referral from a follow‐up physician associated with the first hospital. Seventy‐three percent reported receiving the same tests at both EDs. Interview themes identified multiple health care visits for the same injury, concern about complications, disrespectful treatment at the first ED, delayed care, problems accessing needed follow‐up care without insurance, loss of work, and financial strain. Conclusions: The majority of patients presenting to a public hospital ED after treatment for the same complaint in another local ED were indirectly referred to the public ED without transferring paperwork or records, incurring duplicate testing and patient anxiety.